VD_FINDINFO Arrêt / 2010 / 1209 vom 6. September 2010 - VD Tribunal cantonal (2010)
VENTE DE GRÉ À GRÉ, AUTORISATION OU APPROBATIONEN GÉNÉRAL, AUTORITÉ TUTÉLAIRE | 404 al. 1 CC, 404 al. 3 CC, 420 al. 2 CC, 421 ch. 1 CC